An Aggressive Sphenoid Wing Meningioma Causing Foster Kennedy Syndrome - Harpreet S. Walia; F. Lawson Grumbine; Gagan K. Sawhney; David S. Risner; Neal V. Palejwala; Matthew E. Emanuel; Sandeep S. Walia (Case Reports in Ophthalmological Medicine)
Foster Kennedy syndrome is a rare neurological condition with ophthalmic significance that can manifest as acute visual loss. It is classically characterised by unilateral optic nerve atrophy and contralateral papilledema resulting from an intracranial neoplasm. Physicians should consider Foster Kennedy syndrome in patients who present with visual loss and who have a history of intracranial neoplasm. In addition to ophthalmologic examination, neuroimaging is essential for the diagnosis of Foster Kennedy syndrome.